The Tuck and Shoot Style Vs. The Petrov Model - Bussabarger, D. (Track Coach, 2021)
Each vaulter is an individual, with individual characteristics and tendencies, this should be recognized and addressed when developing his/her technique. For example, should 6`5"/185lb Chris Nilsen have used 5`9¾"/152lb Renaud Lavillenie`s technique as a model for developing his own technique? To quote Nilsen "What works best for me probably won`t work best for Mondo [Duplantis] and what works best for Mondo probably won`t work best for Lavillenie or [Sam] Kendricks. We are all completely different people and have different ways of being successful. To reinforce this point further, here is another quote from Philippe D`Encausse, Renaud Lavillenie`s coach, when asked about the French Model vs. the Petrov Model. "There is no model. Each vaulter has an individual model based on their individual strengths and weaknesses. No athlete is the same, so you have to understand that what is good for one athlete may not be good for another."